PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS PROJECT BASED LEARNING (PjBL) DI SEKOLAH DASAR - Puspita Dewi; Ardiansyah Romadhana; Moch Muzaki; A.F. Suryaning Ati MZ (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
The purpose of this research is to develop Project Based Learning science learning tools. The design of this research is development research. The research subjects in this study were fifth grade elementary school students. The research model used is 4D with four stages of development research namely Define, Design, Development, and Dissemination. However, the implementation of this research is only limited to the development stage. development of project based learning science learning tools to produce learning implementation plans, student worksheets, and project based learning modules that are valid, practical and effective for use in elementary school students. The percentages obtained from each device are lesson plans with a percentage of 95%, LKPD with a percentage of 97%, and Modules 97% so that an average of 96% is obtained with a valid category. Project-based learning-based science learning tools are very effective for elementary school students as evidenced by limited trials and field trials conducted to measure students' responses to the use of project-based learning science-based learning tools. So it can be concluded that the project based learning learning tools for science subjects that have been developed are valid to be used as learning tools in the learning process of students in elementary schools.